Effects of Anticoagulants and Immune Agents on Pregnancy Outcomes and Offspring Safety in Frozen-Thawed Embryo Transfer Cycles—A Retrospective Cohort Study - Fan, Yanli; Wang, Yizhuo; Luo, Zhuoye; Xu, Yueming; Zhang, Jie; Wang, Wei; Cui, Na; Hao, Guimin (Frontiers in Endocrinology, 2022)
The application of anticoagulants and immune agents in assisted reproduction technology has been in a chaotic state, and no clear conclusion has been reached regarding the effectiveness and safety of this treatment. We aimed to explore the potential association between adjuvant medication and pregnancy outcome and offspring safety in a retrospective cohort study including 8873 frozen thawed embryo transfer cycles. The included cycle were divided into three groups according to the drugs used, namely routine treatment group (without anticoagulant agents and immune agents ), anticoagulant agent group and immunotherapy group. Among normal ovulatory patients, those who used immune agents had a 1.4-fold increased risk of miscarriage (≤13 weeks ), but a 0.8-fold decreased chance of birth compared with the routine treatment group. Among patients with more than 1 embryos transferred, those who used anticoagulant agents showed a 1.2-fold higher risk of multiple birth than those undergoing routine treatment. Among patients without pregnancy complications, anticoagulant treatment was associated with a 2.1-fold increased risk of congenital anomalies. Among young patients (< 26 years) with singleton pregnancy, the neonatal birth weight of the immunotherapy group and the anticoagulant treatment group was 305.4 grams and 175.9 grams heavier than the routine treatment group, respectively. In conclusion, adjuvant anticoagulants or immune agents treatment in assisted reproductive technology should be used under strict supervision, and the principle of individualized treatment should be followed.